PELATIHAN PEMANFAATAN AIR KELAPA TUA MENJADI SIRUP DI DESA MAMALA, KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Grace Sipahelut, Sophia (HIRONO : Jurnal Pengabdian Masyarakat, 2024)
The potential for coconuts in Mamala Village, Leihitu District, Central Maluku Regency is quite abundant. However, coconut water, which is part of the coconut fruit, is rarely used and even thrown away, even though old coconut water still contains nutrients that are beneficial for the human body. The aim of this service activity is to increase the knowledge and skills of the people of Mamala Village, Leihitu District, Central Maluku Regency regarding the nutritional content of mature coconut water and how to make coconut water syrup. This community service activity was attended by 25 housewives and young women. This activity stage begins with surveys, counseling, training and evaluation. The outreach activities carried out were able to increase public knowledge about the nutritional content of mature coconut water and how to make coconut water syrup. The training activity aims to improve community skills regarding making coconut water syrup. The evaluation results show that there has been an increase in public knowledge about the material provided.